Egg plants success in Mvara - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2001)
Roy Stephen Muto, teacher of agriculture at Mvara Secondary School in Arua, Uganda, wrote in to 'thank you very much for the good agricultural books you have been mailing me. I also want to say thank you for Spore. With all this literature, my...